Associations of Homelessness with Young Children's Socio-emotional and Educational Functioning: A Risk and Resilience Study - Stargel, Lauren. (Tufts University. Tisch Library., 2020)
Thesis (Ph.D.)--Tufts University, 2020.; Submitted to the Dept. of Child Development.; Advisor: Ann Easterbrooks.; Committee: Tama Leventhal, Sara Johnson, and Janette Herbers.; Keywords: Developmental psychology, Early childhood education, and Behavioral sciences.